Advances in Personalized Targeted Treatment of Metastatic Melanoma and Non-Invasive Tumor Monitoring - Klinac, Dragana; Gray, Elin S.; Ziman, Mel; Millward, Michael (Frontiers in Oncology, 2013)
Despite extensive scientific progress in the melanoma field, treatment of advanced stage melanoma with chemotherapeutics and biotherapeutics has rarely provided response rates higher than 20%. In the past decade, targeted inhibitors have been developed for metastatic melanoma, leading to the advent of more personalized therapies of genetically characterized tumors. Here we review current melanoma treatments and emerging targeted molecular therapies. In particular we discuss the mutant BRAF inhibitors Vemurafenib and Dabrafenib, which markedly inhibit tumor growth and advance patients’ overall survival. However this response is almost inevitably followed by complete tumor relapse due to drug resistance hampering the encouraging initial responses. Several mechanisms of resistance within and outside the MAPK pathway have now been uncovered and have paved the way for clinical trials of combination therapies to try and overcome tumor relapse. It is apparent that personalized treatment management will be required in this new era of targeted treatment. Circulating tumor cells (CTCs) provide an easily accessible means of monitoring patient relapse and several new approaches are available for the molecular characterization of CTCs. Thus CTCs provide a monitoring tool to evaluate treatment efficacy and early detection of drug resistance in real time. We detail here how advances in the molecular analysis of CTCs may provide insight into new avenues of approaching therapeutic options that would benefit personalized melanoma management.